Predicting Body Image Dissatisfaction From Social Media Use and Peer Comparison - Sharma, Neha; Mehta, Rakesh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective:  This study aimed to investigate the predictive roles of social media use and peer comparison on body image dissatisfaction among university students in India.Methods and Materials: The research employed a correlational descriptive design. A total of 491 university students from India participated in the study, with the sample size determined using the Krejcie and Morgan table. Participants completed three standardized self-report instruments: the Body Shape Questionnaire-34 (BSQ-34) to measure body image dissatisfaction, the Social Media Use Integration Scale (SMUIS) to assess social media use, and the Physical Appearance Comparison Scale-Revised (PACS-R) to evaluate peer comparison. Data were analyzed using SPSS version 27. Pearson correlation coefficients were used to examine the relationships between variables, and multiple linear regression analysis was conducted to assess the predictive roles of social media use and peer comparison on body image dissatisfaction. All assumptions for correlation and regression analyses were tested and met.Findings: The results indicated a significant positive correlation between social media use and body image dissatisfaction (r = .41, p < .001), and between peer comparison and body image dissatisfaction (r = .48, p < .001). The multiple linear regression analysis revealed that both social media use (β = .29, p < .001) and peer comparison (β = .36, p < .001) were significant predictors of body image dissatisfaction, explaining 34.2% of the variance in the dependent variable. Peer comparison emerged as a slightly stronger predictor than social media use.Conclusion: The findings underscore the need for educational interventions and mental health strategies aimed at reducing appearance-based social comparison and promoting healthier social media habits to improve body image outcomes.